ANALISIS CORAK HISTORIOGRAFI DALAM KARYA SAGIMUN M.D - Hartutik Hartutik (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2020)
In the scope of history, of course the term historiography is no stranger to the historical method. One of the historiography products in history is the work of Sagimun Mulus Dumadi (Sagimun MD) with entitled "Mas Trip: From the Battle Brigade to the Development Brigade". This paper aims to analyze his work, especially in terms of historiographical features, as well as his presentation of the background, some of his works, and the content of Sagimun MD's book entitled "Mas Trip: From the Battle Brigade to the Development Brigade".